RISE: Sustainability 101 for children / Nur Aini Sabrin Manssor @ Shukri - Sabrin Manssor @ Shukri, Nur Aini (Office of the Deputy Vice-Chancellor (Research & Innovation), 2022)
The environment is vital for life on Earth. Food, water, plants, and minerals are examples of natural resources originating from the environment, and billions of people consume these resources every day. Some resources that people use cannot be replaced once they have been depleted. The world community has noticed that rapid development towards greater civilization has had a great impact on the environment. Therefore, many nations, including Malaysia, have increased their focus on promoting sustainability as a means of protecting and conserving the environment for future generations. In Malaysia, the Ministry of Environment and Water (KASA) is leading the effort toward Sustainable Malaysia 2030.